공공기관 상임감사 채용 과정 개선 방안 연구 : 국립대학교병원 지원 경험 사례를 중심으로 - 홍원일; Hong Weon Il (한국행정연구, 2024)
국립대병원 상임감사를 선임하는 데 있어서 자격, 경력 등 측면에서 적격성이 결여된 인물이 정치적이고 엽관제(獵官制)적 고려에 의해서 임용되고 있다는 비판이 국정감사, 언론 등에서 계속 제기되고 있다. 이 연구에서는 본 연구자가 지원한 5개 국립대병원 상임감사 채용 과정에서의 문제점을 인사행정의 이념인 합법성, 민주성, 형평성, 윤리성 측면에서 분석하여 개선 방안으로 4가지를 제시하였다. 첫째, 합법성 면에서 상임감사 채용 관련 법령의 개정 등 규범 정비, 감사 적격 기준 마련, 개인정보보호법준수, 교육부 장관 임용 근거가 있어야 한다. 둘째, 민주성 이념 면에서 대내·외적으로 공고문 내용의 불명확성을 불식시키기 위해 공고문 내용을 국민의 요구와 시대의 변화, 조직 내 의견수렴을 반영하여 명확하게 기술할 필요가 있다. 셋째, 형평성 이념 면에서 ‘공정’, ‘정의’의 가치가 반영된 서류, 면접전형을 통해 전문성, 윤리성, 리더십 등을 제대로 검증해야 한다. 넷째, 윤리성 이념 면에서 윤리경영을 선도할 상임감사를 채용할 때 윤리성 기준을 제시하고 그에 따른 윤리성 평가가 있어야 할 것이다. 이를 통해 유능하고 윤리성을 갖춘 국립대병원 상임감사를 제대로 채용하여 병원 경영을 바르게 감시하고 견제함으로써 국민들로부터 신뢰받는 국립대병원으로 거듭나길 기대한다. Criticism continues to be raised in the national audit and media that those who lack qualifications and careers in appointing a standing auditor at a national university hospitals are being appointed by political and spoils system. The problems at five national university hospitals that this researcher applied for were analyzed in terms of legality, democracy, equity, and ethics, which are the ideologies of personnel administration, and four improvement measures were suggested. First, in terms of legality, there must be a revision of laws related to hiring standing auditors, establish standards for eligibility for audits, comply with the Personal Information Protection Act and make a ground for the appointment of the Minister of Education. Second, to eliminate the ambiguity of the contents of the notice, it is necessary to clearly describe the contents of the notice by reflecting the needs of the people, changes in the times, and collection of opinions within the organization. Third, professionalism, ethics, and leadership must be properly verified through documents reflecting the values of ‘fair’ and ‘justice’ in terms of the ideology of equity, and interview screening. Fourth, ethics standards should be presented, and ethics evaluation should be made accordingly. Through this, it is expected that it will be reborn as a national university hospital trusted by the public by properly hiring a competent and ethical standing auditor of a national university hospital to properly monitor and check the management of the hospital.